THE INFLUENCE OF BRAND AMBASSADOR, TRUST, PRICE AND PRODUCTS ON PURCHASE DECISIONS AT SHOPEE INDONESIA (CASE STUDY ON PEKANBARU STUDENTS) - Gusdaputra, Damra; Afwa, Awliya; Asril, Asril; Anggraini, Nia (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTShopee is a popular online shopping platform in Indonesia. This platform offers a wide range of products from various sellers, including products specifically targeted towards students. This research was conducted to find out whether there is an Influence of Brand Ambassador, Trust, Price and Product on Purchasing Decisions (case study in Pekanbaru students). The object of this study is Shopee Indonesia with an active student population of universities in Pekanbaru (UNRI, UIR, UMRI, UNILAK and UIN) who have worked at Shopee Indonesia with a sample of 198 people. The sampling technique, namely by  using simple random sampling  using snowball sampling data collection techniques,  the results of this study show that Brand Ambassador and  Trust do not have  a significant effect on purchasing decisions at Shopee Indonesia by Pekanbaru students, while Prices and Products have a significant influence on purchasing decisions on Shopee Indonesia by Pekanbaru students. This research is conducted due to the shift in Indonesian society's shopping behavior, from traditional shopping behavior to digitalization with online buy and sell transactions. The implication of the results of this research is the importance of Shopee providing quality products at prices that meet the desires and target market.Keywords: Brand Ambassador, Trust, Pricing, Products, and Purchasing Decisions